The Solutions of Natural Environmental Degradation in the Perspective of Tafsir An-Nur - Arifuddin, Nur Ilham; Hasan, Abdur Rokhim; Kamaluddin, Ahmad (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
This article examines the solutions to the natural environmental damage from the perspective of Tafsir An-Nur by Teungku Muhammad Hasbi ash-Shiddieqy. The study of natural environmental damage by a contemporary Indonesian mufassir in bil-maâ€™tsur and bir-raâ€™yi style is essential to understand the local interpretation of Al-Qurâ€™an concerning such damage. Through literature study, this research used a descriptive analysis method to describe the perspectives of Tafsir An-Nur regarding verses on the natural environmental damage and the embedded solutions in al-bÄ«â€™ah and fasÄd terms. This article argues that human objectification and greed toward the natural environment are the root of natural environmental damage. Humansâ€™ detachment from the moral-spiritual guidance taught by religion, especially Islam, has led humans to exploitative attitudes toward the natural environment. Tafsir An-Nur offers several solutions to overcome the natural environmental damage, namely interpreting the position of humans as caliphs fairly and wisely, cultivating the qanaâ€™ah character, eliminating hypocrisy in behaving, and building mutualistic relationships toward the natural environment. This article shows that efforts to end the damage to the natural environment begin with humansâ€™ attention to moral-spiritual aspects of ecology.